Management of Anaphylaxis - Agustinus Evrianto Irawan (Global Health Science Group, 2020)
Anaphylaxis is a type-I hypersensitivity reaction which involves various organ system with rapid onset and life-threatening. This reaction present as abnormality on airway, circulation, digestion, and changes of skin and mucose. The aim of this literature review is to explain correct treatment for anaphylaxis. This literature review uses 23 article which were fetched from NCBI and 1 book which are all published in range of year 2000-2020. Keywords used in this literature searching are shock anaphylactic, anaphylaxis, and therapy and publication range filter from 2010-2020 was used. The liiterature searching yielded 4666 articles which were then 23 of them were chosen according to needed information. References were picked and further analyzed with systematic literature review method which consists of collecting, evaluating, and developing the research with certain topics. The result of this review shosws that the administration of epinephrine is key in treating anaphylaxis. Decontamination, evaluation of vital signs, positioning, oxygen therapy, and fluid rescucitation are also vital. Adjuvant therapy with anti-allergy medications should be considered to relieve patient's symptoms